HUMOR AND SATIRE IN WILLIAM SHAKESPEARE'S COMEDIES (Journal of Science-Innovative Research in Uzbekistan, 2024)
This abstract examines the various facets of satire and humor in William Shakespeare's comedies. By examining a few plays, such as "Twelfth Night," "A Midsummer Night's Dream," and "Much Ado About Nothing," we look at how Shakespeare uses a variety of comedic tropes, like situational humor, physical comedy, and verbal wit, toboth amuse audiences and provide insightful commentary on human nature and society norms. This abstract illuminates the lasting relevance of Shakespearean humor and its ability to resonate with audiences across time and culture by exploring the interplay between laughter and critique